Physical activity for children up to 5 years old: Physical Activity Guidelines for the Brazilian Population - Silva, Larissa Rosa da (2021)
This paper describes the process of establishing physical activity recommendations for children up to five years old included in the Physical Activity Guidelines for the Brazilian Population. The development of these recommendations was based on the guidelines proposed by the World Health Organization in 2019. Theoretical support was gathered by using the following strategies: scoping review conducted to update the body of knowledge about the correlates and determinants of physical activity in children 0-5 years old; 2-synthesis of the existing national physical activity guidelines; 3-online interviews with parents and teachers aiming to identify their degree of difficulty in understanding the recommendations contained in the World Health Organization Physical Activity guidelines and to identify barriers and strategies for improving the involvement of children in physical activities; and, 4-public consultation. All actions were developed in the period from May to December 2020, by a working group composed of researchers with expertise in this field and representatives of the Ministry of Health. As a result, a total of 35 recommendations were included in the Brazilian guidelines, 10 of which were related to benefits, four to the dose, seven to the types of activities, seven to the strategies for improving practice, and seven others related to the reduction of sedentary behavior. When relevant and possible, these recommendations were differentiated for children from birth to one year of age, 1-2 years, and 3-5 years. The main message is that any physical activity is better than none and that sedentary behavior should be reduced.